"x^{2}y'' - xy' = lnx"
"y' = p(x), y'' = p'(x)"
"x^{2}p' -xp = lnx"
"p = uv, p' = u'v + uv'"
"x^{2}(u'v + uv') - xuv = lnx"
"v(x^{2}u' - xu) + x^{2}uv' = lnx"
"x^{2}u' - xu = 0, u=x"
"x^{3}v' = lnx"
"v = \\int \\frac{lnx}{x^{3}} dx = [x = e^{p}, dx = e^{p}dp, lnx = p] = \\int pe^{-2p}dp = - \\frac{1}{2}(pe^{-2p} -\\int e^{-2p}dp)="
"=- \\frac{1}{2}(pe^{-2p} +\\frac{1}{2}e^{-2p}) = [x=e^{p}] = -\\frac{1}{2x^{2}}(lnx+\\frac{1}{2} + c)"
"y' = p = uv = -\\frac{1}{2x}(lnx+\\frac{1}{2} + c)"
"y = \\int -\\frac{1}{2x}(lnx+\\frac{1}{2} + c)dx = \\int -\\frac{lnx}{2x} dx - \\frac{1}{4}ln|x|- \\frac{c_1}{2} ln|x| + c_2="
"- \\frac{ln^{2}|x|}{4} - \\frac{1}{4}ln|x|- \\frac{c_1}{2} ln|x| + c_2"
Comments
Leave a comment